Expounding the Diversity of African Construction of Fertility: the Yorùbá Example - IBRAHIM Fausat Motunrayo (Ученые записки Института Африки Российской академии наук)
While African population dynamics are typically referenced even in global demographic discourses, there is indeed a dearth of interpretive understanding of cultural construction of fertility among African ethnic groups. This article is a report of an ethnologic exploration of indigenous construction of fertility among rural Yorùbá farmers. Farmers were targeted because of their surviving ‘traditionality’ amongst other factors. Findings validate the commonplace assumption underscoring pro-fertile African value for children. More interestingly, findings yielded low-fertility compliant and even neutrality-laden fertility-related Yorùbá cultural construction. Among other things, findings demonstrate that the character of fertility-related Yorùbá construction is adaptive, empathetic and integrative, thereby affirming that the traditional veneration of the fertile is huge but non-sacrosanct.